LaNi5 hydride powder flowability as a function of activation and hydrogen content - Melnichuk, Maximiliano (2017)
Volume expansion of hydrogen absorbing materials, together with inter-particle friction can cause tension accumulation in hydride containers during absorption. When hydride particles absorb hydrogen there is an important volume increase, in the order of 25%. Particles have to accommodate to the container geometry but this movement is opposed by inter-particle friction. Under certain conditions tensions can build up, compromising the mechanical integrity of the container. This phenomenon needs to be addressed at the design stage to avoid mechanical failure of the container. Flow behavior of powder materials is a relevant technological field, usually addressed by means of qualitative or quantitative flowability measuring devices. The rotating drum technique, while mainly qualitative, is well established and can be modified into a completely sealed unit. To determine the flowability of a hydride under different activation stages and hydrogen content levels we developed a rotating drum device that can be pressurized with hydrogen or depressurized. We report particle size evolution and flowability measurements of a hydrogen absorbing material (LaNi5) at different stages of activation for both absorbed and desorbed states. The results of the present study show that the flowability of LaNi5 in more dependent on the degree of activation of the sample than on hydrogen absorption state.